Pharmacogenetics of CYP450A, ABCB1, ABCC2, SLCO1B3 gene polymorphisms and plasma alpha-1-acid glycoprotein level on nonhaematological adverse events of docetaxel in Malaysian breast cancer patients - Jabir, Rafid Salim (2015)
Docetaxel is an antitubulin chemotherapeutic agent approved for the treatment of breast, lung, ovarian and non-hormonal dependent prostate cancers. However, the success of this drug is limited by adverse events (AEs), the severity of which ranges from tolerable to life threatening. Tapering the dose or changing the regimen would limit the use of docetaxel. Therefore, the present study was conducted involving 110 Malaysian breast cancer patients of different ethnic groups (Malays, Chinese and Indians) to investigate the association between docetaxel AEs and single nucleotide polymorphisms (SNPs) of genes encoding for proteins involved in the metabolism and transport of docetaxel. In addition, the present study investigated the association of plasma levels of alpha-1-acid glycoprotein (AAG) with docetaxel-induced non-haematological AEs. Eligible consented patients enrolled in the study were recruited from University Malaya Medical Centre (UMMC) and Universiti Kebangsaan Malaysia Medical Centre (UKMMC). The ethnicity of breast cancer patients in this study consisted of 40% Malays (n=44), 52% Chinese (n=57) and 8% Indians (n=9). Fatigue (50%), nausea (35%) and oral mucositis (31%) were the most commonly reported non-hematologic AEs. The SNPs of enzyme cytochrome P450 3A5 (CYP3A5 6986A>G), and transporters ATP-binding cassette (ABCB1 3435C>T, ABCB1 2677G>T/A and ABCC2 1249G>A) as well as solute carrier organic anion transporter (SLCO1B3 334T>G) had significant influence on the development of docetaxel AEs. Rash was significantly associated with ABCB1 3435CTpolymorphism: 36% of Chinese patients who were carriers of heterozygous genotype developed rash, while it only occurred in 21% of Malay carriers. It is worth noting that the Indians did not develop rash although 44% of them had heterozygous genotype. As such, it can be said that Chinese who are carriers of the heterozygous genotype are at high risk of developing rash. Moreover, since the heterozygous and mutant genotypes showed higher prevalence than the wild type, the toxicity effect (rash) is very likely related to mutant allele (T). Interestingly, the wild type GG of ABCB1 2677GA was associated with fatigue in 60% of Malays, 53% of Chinese and 33% of Indians. However, the difference among the ethnic groups was not statistically significant. Oral mucositis was associated with the coexistence of CYP3A5 6986AA (wild type) and ABCB1 3435TT (mutant). Low plasma levels of AAG were significantly associated with rash and oral mucositis caused by docetaxel. This study indicates SNPs-AEs associations could be used to individualise treatment to reduce AEs of docetaxel in Malaysian breast cancer patients.